Pengaruh Media Tanam dan Jenis Tanaman Terhadap Produksi Nutrien Bagian Aerial Tanaman Sorgum dan Jagung - Cahyono, Budi Dwi; Sudiyono, Sudiyono; Handayanta, Eka (Universitas Sebelas Maret (UNS), 2018)
This research aims to know the biogas sludge utilization on planting media by looking at the difference in production of sorghum and maize crops. This research was conducted on November 2015 until January 2016 in the area around cultivation of Izzah Sejahtera Farm cattle farm, Jagoan Village, Sambi District, Boyolali District. The material used is planting land, sludge biogas, sorghum and corn seed. The research design used was a complete randomized design of 2 x 2 factorial pattern. The research consisted of two treatment factors namely plant effect (Factor A) and difference of land type (Factor B). Plant factor consists of 2 levels, namely sorghum and corn. Land type difference factor consists of 2 levels, ie land without sludge biogas and land with sludge biogas. The treatment in this study, namely T1P0: Sorgum grown on soil without sludge biogas, T1P1: Sorgum grown on soil with sludge biogas, T2P0: Corn grown on soil without sludge biogas, T2P1: Corn grown on soil without sludge biogas . Each plant consists of 96 plants divided into two, P0: 48 plants and P1: 48, so there are 192 units of experiment. The data obtained were analyzed by analysis of variance to know the difference of treatment to the observed variables based on F test of 5% level and if there is a significant difference then continued to analyze with Duncan's Multiple Range Test (DMRT) 5%.